Clinical and laboratory status in Parkinson’s disease patients with and without polyneuropathy - Popović, Sanela; Popović, Nemanja; Hajder, Dragica; Kostic, Smiljana; Lučić Prokin, Aleksandra (Vojnosanitetski pregled, 2024)
Background/Aim. The etiology of polyneuropathy (PNP) in patients with Parkinson’s disease (PD) is unclear, and there is a possible association between levodopa therapy, hyperhomocysteinemia, and PNP development due to methylation processes involving vitamin B12 and folic acid.  The aim of this study was to analyze the difference in clinical presentation and disease severity between PD patients with and without PNP and to evaluate blood levels of vitamin B12, homocysteine, and folic acid in these patients. Methods. This cross-sectional study included 200 consecutive patients diagnosed with PD, divided into two groups: those with PNP and those without PNP. Diagnosis of PNP was confirmed by electromyoneurography. The first group consisted of 50 patients with PD with confirmed PNP, and the second 50 patients with PD without PNP. All patients were receiving levodopa therapy. Laboratory tests analyzed vitamin B12, folic acid, and homocysteine levels. Results. Patients with PNP were older when PNP was diagnosed (71 vs. 66 years, p
Keywords: age factors; levodopa; parkinson’s disease; polyneuropathies; severity of illness index; vitamin b 12